Long-period variability in ice-dammed glacier outburst floods due to evolving catchment geometry - Jenson, Amy; Amundson, Jason M.; Kingslake, Jonathan; Hood, Eran (Copernicus Publications on behalf of the European Geosciences Union, 2022)
We combine a glacier outburst flood model with a glacier flow model to investigate decadal to centennial variations in outburst floods originating from ice-dammed marginal basins. Marginal basins can form due to the retreat and detachment of tributary glaciers, a process that often results in remnant ice being left behind. The remnant ice, which can act like an ice shelf or break apart into a pack of icebergs, limits a basin’s water storage capacity but also exerts pressure on the underlying water and promotes drainage. We find that during glacier retreat there is a strong, nearly linear relationship between flood water volume and peak discharge for individual basins, despite large changes in glacier and remnant ice volumes that are expected to impact flood hydrographs. Consequently, peak discharge increases over time as long as there is remnant ice remaining in a basin, and peak discharge begins to decrease once a basin becomes ice-free. Thus, similar size outburst floods can occur at very different stages of glacier retreat. We also find that the temporal variability in outburst flood magnitude depends on how the floods initiate. Basins that connect to the subglacial hydrological system only after reaching flotation depth yield greater long-term variability in outburst floods than basins that are continuously connected to the subglacial hydrological system (and therefore release floods that initiate before reaching flotation depth). Our results highlight the importance of improving our understanding of both changes in basin geometry and outburst flood initiation mechanisms in order to better assess outburst flood hazards and their impacts on landscape and ecosystem evolution. This project was supported by funding from the Alaska Climate Adaptation Science Center and the US National Science Foundation (OIA-1757348 and OPP-1743310). We thank Christian Kienholz for fruitful discussions that led to this study Yes